Causation, Spending, and Taxes: Sand in the Sandbox or Tax Collector for the Welfare State? - Hoover, Kevin D.; Sheffrin, Steven M. (American Economic Review, 1992)
Causal relations between federal expenditure and taxation are analyzed using an approach based on the invariance of econometric relationships in the face of structural interventions. Institutional evidence for interventions or changes of regime combined with econometric tests for structural breaks are used to investigate the relative stability of conditional and marginal probability distributions for each variable. The patterns of stability are the products of underlying causal order. We find two distinct causal structures operating in the postwar era. Before the mid-1960's, taxes appear to cause spending. After the late 1960's, taxes and spending are causally independent.